Logistics in the Peruvian Armed Forces and their Contribution to National Defense and Development - Morales Mendiguetti, Nestor (2019)
The main objective of the study was to determine to what extent logistics in the Armed Forces of Peru contribute to National Defense and Development. The investigation was descriptive and the level of application, with a study population represented by 315 officers of the Logistics Command of the Peruvian Army and a sample of 172 officials. A survey-level questionnaire was used as an instrument in the empirical test, in addition to the Chi-square Test for the demonstration of the following Hypothesis: Logistics in the Peruvian Armed Forces contributes significantly to National Defense and Development. After developing the investigation, it was concluded that the level of logistics achieved in the Armed Forces of Peru contributes significantly to the National Defense and Development.